PENERAPAN MEDIA KOMIK CERITA RAKYAT UNTUK MENINGKATKAN MINAT MEMBACA SISWA KELAS IV MADRASAH IBTIDAIYAH - Ivan Pratama, Ade; Minnah El Widdah; Sean Popo Hardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading interest among elementary school students in Indonesia remains low, and this condition was also found among fourth-grade students at Madrasah Ibtidaiyah Nurul Hidayah, Jambi City, particularly in reading folklore texts. Students tended to be less enthusiastic, easily bored, and more attracted to picture-based reading materials than plain text. This classroom action research aimed to determine whether the use of comic media could increase students' interest and ability in reading folklore. The study followed the Kemmis and McTaggart model, consisting of a pre-cycle stage and two action cycles (Cycle I and Cycle II), each comprising planning, action, observation, and reflection. The subjects were 31 fourth-grade students. Data were collected through interviews with the principal, class teacher, and students, reading comprehension tests, observation sheets, and documentation, then analyzed descriptively and quantitatively using mean and percentage formulas. The results showed that students' average reading score increased from 41.12% (very poor category) in the pre-cycle to 86% (good category) in Cycle I, and 87% (good category) in Cycle II, with the percentage of students reaching the completeness criterion rising from 12.9% to 96.8%. Improvement was also evident in the accuracy, pronunciation, and fluency indicators. These findings indicate that comic media, which combines engaging illustrations with folklore narratives, is effective in increasing elementary students' reading interest and reading ability.